If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2x + -15 = 84 Reorder the terms: -15 + 9x + 2x = 84 Combine like terms: 9x + 2x = 11x -15 + 11x = 84 Solving -15 + 11x = 84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 11x = 84 + 15 Combine like terms: -15 + 15 = 0 0 + 11x = 84 + 15 11x = 84 + 15 Combine like terms: 84 + 15 = 99 11x = 99 Divide each side by '11'. x = 9 Simplifying x = 9
| 4x+16-2x=32 | | 18=3c+12-c+4 | | 4y-6=14y+84 | | -7x-3+3x=-47 | | 14x-7x-9=12 | | 130=2(7d-5) | | 2=7x-7x | | 3/5+a=-2/5 | | 5a+7a=-24 | | 2x-8+x=7 | | r^2+3r=8 | | 25=-2a-8a | | 5x^2=17x-2 | | 92=-4(2m-2)-4m | | 8x+2x-18=32 | | 2(1/3)x+5=19 | | 8x+12y=80 | | 18=5x+3 | | 92=-4(2n-2)-4m | | 2y^2+7y=0 | | -10=6p-4p | | 6x-6=8x-28 | | 2y^2+6=-7y | | (x+5)(4x+1)=-15 | | (5+4t)(8-5t)=0 | | 4=r+7-2 | | 48/2 | | (x+5)(5x+1)=-19 | | 5(x^2-12x)+4x(7-3x-2x^2)= | | 3y(5y^2-8)= | | 2x+3x+12=27 | | 8+6x-3x=29 |